2019
DOI: 10.1021/acs.jpcb.9b00654
|View full text |Cite
|
Sign up to set email alerts
|

Stability and IR Spectroscopy of Zwitterionic Form of β-Alanine in Water Clusters

Abstract: Amino acids are the building blocks of proteins, and their detection in outer space thus has implications on the origin of life. They form a zwitterionic structure in aqueous environments while adopting a neutral configuration in the gas phase. We perform an experimental and computational study on the number of water molecules needed for zwitterion formation of β-alanine. Our density functional theory investigation reveals that a minimum of five water molecules are required to form and stabilize the zwitterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Nevertheless, the "trapped water" molecule is in similar spirit as the "connecting water" molecule in the recent experimental and theoretical findings. 37 Crittenden et al 15 also found a molecular bridge of one or two water molecules for GABA• 2H 2 O and GABA•5H 2 O. Thus, the results of the current study capture some of the features of existing studies.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, the "trapped water" molecule is in similar spirit as the "connecting water" molecule in the recent experimental and theoretical findings. 37 Crittenden et al 15 also found a molecular bridge of one or two water molecules for GABA• 2H 2 O and GABA•5H 2 O. Thus, the results of the current study capture some of the features of existing studies.…”
Section: Resultssupporting
confidence: 80%
“…We note here that, although the favorable electrostatics have the tendency to trap more water molecules, spatial constraints forbid the same. A recent experimental and theoretical study 37 on microsolvated β-alanine shows the existence of "connecting water" between the carboxylate and amino groups. The "connecting water", which is similar to the trapped water molecule in the current study, is found to enhance the stability of the zwitterionic β-alanine.…”
Section: Resultsmentioning
confidence: 99%
“…The huge amount of water at the earth's surface supports a multitude of dissolved gases and nano-particles that are significant in climate change; cf., for instance, black carbon [2]. Further issues related to water are the behaviour of oil films [3], the synthesis of nano-materials for medical applications [4,5], the behaviour of two-dimensional materials [6], and the behaviour of colloidal suspensions [7,8]. The functional mechanism of membranes [9,10] is also a relevant class.…”
Section: Introductionmentioning
confidence: 99%
“…The huge amount of water at the earth’s surface supports a multitude of dissolved gases and nanoparticles that are significant in climate change, cf., for instance, black carbon . Further issues related to water are the spreading of oil films, synthesis of nanomaterials for medical applications, , formation of two-dimensional materials, and stability of colloidal suspensions. , The functional mechanism of membranes , is also a relevant class. The description of all these systems requires good knowledge of the dielectric function of water on the real frequency axis as well as, for calculation of van der Waals interactions, imaginary frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, a discrete model was selected by using IR spectroscopy and DFT calculations of tryptophan structures in their zwitterionic form within clusters of Trp-(H 2 O) n with n ≥ 5 [12]. For β-Alanine, Ghassemizadeh et al [16] show a direct transfer of protons from the amino group to the carboxyl group with five and six molecules of water, which change the Trp molecule from a neutral to a zwitterionic form, thereby leading to two bonds that give rise to the COO − and 3 NH + components. These molecules of water form as many hydrogen bonds as possible between them and the zwitterion, so that an additional hydrogen-bonded wire is formed between the charged poles with seven and eight molecules of water.…”
Section: Introductionmentioning
confidence: 99%